Metabolic and Hormonal Profile of Adolescent Girls With Polycystic Ovary Syndrome With Concomitant Autoimmune Thyroiditis - Skrzyńska, Karolina Joanna; Zachurzok, Agnieszka; Gawlik, Aneta Monika (Frontiers in Endocrinology, 2021)
Introduction: Both polycystic ovary syndrome (PCOS) and autoimmune thyroiditis (AT) are considered to be one of the most common endocrinopathies in young women and they are classified as diseases that affect many processes in the human body. Their role in the development of metabolic disorders and diseases of the cardiovascular system in adult women is also emphasized. However, there are no data available to assess such risk in the teenage girl population. The aim of the study was to assess the hormonal and metabolic profile of adolescent girls with PCOS, additionally diagnosed with AT, as well as an attempt to identify a group of PCOS patients with the highest risk of AT. Material and methods: 80 euthyroidic PCOS patients were qualified for the study (chronological age 16.54±1.00 years, BMI 24.60±4.16 kg/m2). 18 girls diagnosed with AT were included in the study group and 62 girls without AT - in the control group. Each patient had biochemical and hormonal tests performed. Additionally, in order to diagnose AT, the level of antibodies against thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg), as well as the image of the thyroid gland on ultrasound examination, were taken into account. Results: The estradiol concentration was significantly higher in the study than in the control group (203.00±217.00 vs. 152.00±78.50 pmol/l, p=0.02). Higher DHEAS concentrations were also observed in the AT group compared to the group without AT (391.28±176.40 vs. 317.93±114.27 µg/dl, p=0.04). Moreover, there was a positive correlation between anti-TPO and estrogen concentration (ry=0.27; p=0.04). It was also shown that there is a tendency towards statistical significance for the positive correlation between the positive anti-TPO titer and the glucose concentration at 120 min. OGTT (rƴ=0.26; p=0.07), and girls with PCOS and AT had higher glucose levels in 120 min. OGTT (115.2941.70 vs. 98.5628.02 mg/dl, p=0.08). Conclusion: The results of these studies may suggest that girls with PCOS at risk of high exposure to estrogens i.e. obese with chronic anovulatory cycles seem to be a special group in which we should consider the possibility of AT.